Pengaruh Gaya Hidup Dan Persepsi Konsumen Terhadap Keputusan Pembelian Handphone iPhone Pada Mahasiswa UHN Medan - Manurung, Lastaria; Sihombing, Natalia E.; Degodona, Primawati (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the influence of lifestyle and consumer perception on iPhone purchasing decisions among students at HKBP Nommensen University, Medan. The formulation of the problem in this study is whether there is an influence of Lifestyle and Consumer Perception on Consumer Purchasing Decisions for Samsung Smartphones with a research population of HKBP Nommensen University Medan Students and a sample taken using the Snowball sampling approach of 100 people.Based on the results of hypothesis testing, it can be concluded: The results of simultaneous hypothesis testing with the significance value of the F test on variables X₁, and X2 are 0.000<0.05 and the Fcount value is 183.042 Ftable (Ftable, n-k-2; 98). 2.70. The results of the determination coefficient test show that there is an influence of Lifestyle and Consumer Perception on the Purchase Decision for the iPhone by 79.1% and the rest is influenced by other factors not examined in this study.